2022
DOI: 10.3390/cells11223690
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathways Regulating Human Cervical Ripening in Preterm and Term Delivery

Abstract: At the end of gestation, the cervical tissue changes profoundly. As a result of these changes, the uterine cervix becomes soft and vulnerable to dilation. The process occurring in the cervical tissue can be described as cervical ripening. The ripening is a process derivative of enzymatic breakdown and inflammatory response. Therefore, it is apparent that cervical remodeling is a derivative of the reactions mediated by multiple factors such as hormones, prostaglandins, nitric oxide, and inflammatory cytokines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 180 publications
0
6
0
Order By: Relevance
“…With regard to Hsp70, previous studies have reported elevated levels in the serum of women with preeclampsia compared to those with normal pregnancy [53,54], as well as in vaginal fluid of women with short cervix, suggesting its involvement in the proinflammatory cervico-vaginal milieu leading to cervical shortening [39]. The lower plasmatic concentration of Hsp70 observed in women with short cervix in this study may be attributed to the recall of the pro-inflammatory cells and molecules to the shortening cervix, where they play a role in the cervical tissue remodelling [39,49,55].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…With regard to Hsp70, previous studies have reported elevated levels in the serum of women with preeclampsia compared to those with normal pregnancy [53,54], as well as in vaginal fluid of women with short cervix, suggesting its involvement in the proinflammatory cervico-vaginal milieu leading to cervical shortening [39]. The lower plasmatic concentration of Hsp70 observed in women with short cervix in this study may be attributed to the recall of the pro-inflammatory cells and molecules to the shortening cervix, where they play a role in the cervical tissue remodelling [39,49,55].…”
Section: Discussionmentioning
confidence: 60%
“…MMP-8 and other MMPs play crucial roles in cervical remodelling, and their concentration and activity have been reported to increase in the lower uterine segment during labor [48]. We hypothesize that the lower plasma MMP-8 levels observed in pregnant women with a short cervix may be associated with higher levels of this enzyme in the placenta or in the lower uterine segment, where inflammation and remodelling may occur [49]. MMP-8 has been shown to compromise epithelial barrier integrity [47] and its levels in vaginal fluid have been associated with cervical shortening [39].…”
Section: Discussionmentioning
confidence: 92%
“…The ripening is a process derivative of enzymatic breakdown and inflammatory response. Therefore, it is apparent that cervical remodeling is a derivative of the reactions mediated by multiple factors such as hor-mones, prostaglandins, nitric oxide, and inflammatory cytokines [11].…”
Section: About Mifepristone About Mifepristonementioning
confidence: 99%
“…Collagenous tissue is an important structural biomaterial in most multicellular animals. The mechanical properties of collagenous tissue are usually relatively stable, with any significant non-pathological changes taking place over timescales of days (during relaxation of the mammalian uterine cervix [1]) to years (during maturation and ageing [2]). However, all five living classes of the phylum Echinodermata (sea lilies and featherstars, sea-urchins, sea-cucumbers, starfish, brittlestars) possess collagenous tissue that can drastically alter its mechanical properties within a timescale of seconds under the direct control of the nervous system.…”
Section: Introductionmentioning
confidence: 99%